Development of Technology for the Production of Grease Based on Local and Secondary Raw Materials (Texas Journal of Engineering and Technology, 2022)
The article investigates the possibility of obtaining a plastic lubricant based on secondary raw materials and local raw materials. Obtaining grease from waste allows replacing industrial raw materials, which will affect the economy of their production. At the same time, the use of waste ensures the environmental safety of the environment. The resulting grease in laboratory conditions is not inferior to general-purpose lubricants in terms of its quality.